Trust Based Authentication Mechanism in Wireless Sensor Networks - Ru-ping, Li (International Journal of Online and Biomedical Engineering (iJOE), 2016)
Authentication mechanism is the basis of access control and data exchange. In wireless sensor networks, the vulnerability of network nodes and complexity of communication protocols pose a huge challenge for designing authentication mechanism in such environment. In this paper, we study the authentication mechanism in wireless sensor networks based on trust between nodes. We use the interaction history of nodes for recommendation trust computation, and the interaction history comes from the interactions between nodes. We design a penalty mechanism for hostile nodes based on the TCP congestion control protocol, and present a loyalty based trust recommendation evaluation algorithm. Massive experiments validate the efficiency and effectiveness of the proposed approach.